Analysis of EFL Students' Ability in Reading Vocabulary of Synonyms and Antonyms - Vina Fathira (Universitas Lancang Kuning, 2017)
Reading is an important thing for academic level. Every student must have many vocabularies to encourage her/his reading skill. The aim of this research is to analyze the students' understanding of reading vocabularies of synonyms and antonyms in the higher education level. Synonyms and antonyms are two important things should be mastered to get better reading comprehension. The method used in this research was quantitative with survey design. The population same as the sample of this research was from fifth semester students of STIBA Persada Bunda Pekanbaru. The procedures of the research were divided into 3 parts. First, students were asked to choose the best choice in the multiple choice for synonyms and anton, number and the wrong number, and grouped the wrong number into difficulties level. Last, the researcher analyzed the students' ability in reading vocabulary of synonyms and antonyms and concluded the result of students' ability in reading vocabulary of synonyms and antonyms in elementary, intermediate, and advanced level. The result of this research showed that the students' ability in reading vocabulary of synonyms and antonyms was categorized into "excellent" level with mean score 85. From the three difficulties level of question, the findings of this research were explained every level of question. In synonyms, the mean score of students' ability were 89, 85, and 84 for elementary, intermediate, and advanced level of question. Whereas, in antonyms, the mean score of students' ability were 97, 85, and 69 for elementary, intermediate, and advanced level of question. Keywords: students' ability, reading vocabulary, synonyms and antonyms